Finite-temperature dynamical structure factor of alternating Heisenberg chains - James, A; Essler, F; Konik, R (2008)
We develop a low-temperature expansion for the finite-temperature dynamical structure factor of the spin half Heisenberg chain with alternating nearest-neighbor exchange in the limit of strong alternation of the exchange constants. We determine both the broadening of the low-lying triplet lines and the contribution of the thermally activated intraband scattering. © 2008 The American Physical Society.